Assessment of the Momentum Balance Method for Determination of Shear Stress in Compound Meandering Channels - V. Moratzavi Amiri; K. Esmaili (مهندسی عمران شریف)
Shear stress is one of the most essential factors in the flow dynamics of open channels. The hydraulics of sediment transport in channels are affected by how and the amount of this factor. Considering the three-dimensional and complex nature of the flow in meandering compound channels, and based on the effective role of secondary flows and momentum transfer, especially in curves, calculating this parameter using the methods provided for straight channels is challenging. The Momentum Balance Method, introduced as one of the shear stress determination methods in straight channels, can be used to determine the shear stress in meandering channels. In this research, using the 3-D flow velocity component data measured by ADV, the distribution of shear stress along the flow path in a meandering compound channel was investigated. The transverse distribution of streamwise velocity was investigated in a physical model, including a rectangular concrete channel, a meandering main channel, and two floodplains. Then, the transverse distribution of shear stress in five sections along the flow was calculated using the momentum balance method, and the results were compared using the logarithmic distribution method of velocity and Reynolds shear stress in these sections. Also, the amount of shear stress at four depths of the main channel is illustrated. Since the determination of maximum shear stress areas can be effective in flow and sediment studies, and issues related to river maintenance, such as bed erosion, especially in arches, the maximum values of relative shear stress in MBM, RSM, and LLM methods were determined as 5.43 and 7.24 in the fourth section and 6.05 in the first section, respectively. The minimum amounts of shear stress were observed in section 5 in both RSM and MBM methods. According to the reviewed results, the MBM method can be introduced as a practical method for evaluating shear stress values in meandering rivers.